Risk assessment vs real prediction: The prediction problem and public trust - Shannon, Lyle W. (Journal of quantitative criminology, 1985)
Confusing risk assessment and the prediction of individual behavior has led to false claims which, if translated into juvenile court or adult sentencing policies (selective incapacitation, for example), may lead to further erosion in public confidence in the justice system. Considerable emphasis has been placed on the consequences of false positives in the literature and in this paper. The false negative has different but equally damaging effects because the impression may be given that increasing the severity of sanctions for selected serious offenders is the solution to juvenile delinquency and adult crime. Analysis of official police records for three birth cohorts from Racine, Wisconsin, reveals that, although high-risk groups produce a disproportionate share of the delinquent and criminal behavior recorded in police reports and juveniles in high-risk groups continue into adult crime disproportionately to others, serious juvenile offenders still account for only a portion of the serious offenses that will ultimately be committed by adults. Therefore, selective incapacitation of early offenders may take only a small bite out of crime. When referrals rather than police contacts were utilized as the predictor variable, there was little difference in predictive efficiency.